Childhood height increases the risk of prostate cancer mortality. Issue 10 (July 2015) - Aarestrup, J.; Gamborg, M.; Cook, M.B.; Baker, J.L.
Abstract Background Adult body size is positively associated with aggressive and fatal prostate cancers. It is unknown whether these associations originate in early life. Therefore, we investigated if childhood height, body mass index (BMI; kg/m2) and growth are associated with prostate cancer-specific mortality and survival. Methods Subjects were 125, 208 men from the Copenhagen School Health Records Register, born 1930–1969 with height and weight measurements at ages 7–13 years. Linkage to the Danish Cancer Registry and the Register of Causes of Death enabled identification of incident and fatal prostate cancers. Cox proportional hazards regressions were performed. Results 630 men had prostate cancer recorded as the underlying cause of death. Childhood height at age 13 years was positively associated with prostate cancer-specific mortality (hazard ratio [HR]per z-score = 1.2, 95% confidence interval [CI]: 1.1–1.3). Associations were significant at all other childhood ages. Growth analyses showed that height at age 13 years had a stronger association with prostate cancer-specific mortality than height at age 7, suggesting the association at age 7 is largely mediated through later childhood height. The tallest boys at age 13 years had a significantly worse survival, but only when restricted to a diagnosis at <60 years of age (HRz-score of 1 = 1.7, 95% CI: 1.3–2.4). These associations were significant at all other childhood ages. Childhood BMI was not associated with prostate cancer mortality or survival. Conclusion Childhood height was positively associated with the hard end-point of prostate cancer-specific mortality, which strengthens prior epidemiologic observations of a positive association with prostate cancer incidence.